Streamlining Oracle HCM Cloud Processes: Integrating VBCS and OIC for Enhanced Efficiency - Manivannan Ramar, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
This comprehensive article examines the transformative impact of integrating Visual Builder Cloud Services (VBCS) and Oracle Integration Cloud (OIC) with Oracle HCM Cloud. The article explores how the introduction of Redwood design has revolutionized enterprise cloud applications, enabling seamless collaboration and enhanced operational efficiency. Through analysis of multiple enterprise implementations, the article demonstrates significant improvements in document management, workflow automation, and user experience. The article covers technical implementation strategies, security considerations, and best practices while highlighting substantial benefits in operational efficiency, cost savings, and user empowerment. The article particularly focuses on real-world applications, including ACH file review systems and employee promotion processes, providing concrete evidence of the integration's value in modern enterprise environments.
Keywords: Cloud Integration; Enterprise Systems; HCM Transformation; Oracle Technology; Workflow Automation